KAJIAN PENETAPAN KAWASAN PEMUKIMAN KUMUH DI KAWASAN BANTARAN SUNGAI KAHAYAN - Ludang, Yetrie; Firlianty, Firlianty; Rario, Rario; Elita, Elita; Bugar, Natallo; Grestyana, Nadya; Ludang, Ellydia; Mentari, Theresia; Najamuddin, Anang (EnviroScienteae, 2023)
Slum settlements are organizations that are unfit for habitation because of uneven buildings, high construction density, and unsatisfactory quality of buildings, facilities and infrastructure. The objectives of this research are: (1) Identify and identify residential areas located on the banks of the Kahayan River, Pahandut Seberang Village, Palangka Raya City. (2) Analysis of factors influencing the development of slum organizations in the Kahayan riverbank area, Pahandut Seberang sub-district, Palangka Raya city. The sampling method in this research was carried out by collecting data on the number of houses located within a 50m radius of the river boundary. From this data, processing is then carried out according to the Slovin formula.